APOCALYPSES NOW: MODERN SCIENCE AND BIBLICAL MIRACLES: THE BOYLE LECTURE 2018: with Mark Harris, "Apocalypses Now: Modern Science and Biblical Miracles: The Boyle Lecture 2018"; John Hedley Brooke, "The Ambivalence of Scientific Naturalism: A Response to Mark Harris"; and Mark Harris, "On 'the Natural Nature of Naturalism': Answers to John Hedley Brooke's Questions.". Issue 4 (21st November 2018) - Harris, Mark
Abstract: I explore an intriguing area that has crept under the radar of today's science‐and‐theology conversation, namely, scientific studies of the big miracle and catastrophe stories of the Bible (e.g., Noah's flood, or the plagues of Egypt). These studies have proposed naturalistic explanations for some of the most spectacular and unlikely of the biblical miracles. While the scientists believe their naturalistic interpretations represent a major advance in understanding the stories, professional biblical scholars show little interest, or are openly disdainful. I will point out the striking parallels with the foundational "catastrophism‐uniformitarianism" controversy in nineteenth‐century geology, and will suggest that the debate also takes us toward a novel kind of natural theology when we consider the biblical miracle and catastrophe texts. Here, the spectacular scientific explanations do not deny the miraculous character of the biblical stories so much as provide a uniquely modern purchase on their transcendent quality.